Trend Analysis of Relative Poverty in Pakistan (1984-85 - 1987-88) (The Pakistan Development Review, 1994)
In this paper, we compare poverty statistics for Pakistan based on data from the Household Income and Expenditure Surveys of 1984-85 and 1987-88, using a relative concept of poverty. After a brief look at the quality of the surveys in use in Section II we recapitulate the relative poverty concept in Section III. In Section IV we compare the size and composition of the poor population in 1984-85 and 1987-88 by using relative poverty lines. In Section V we extend the analysis by differentiating results across rural and urban areas and by taking into account that the cost of living in rural areas may be lower than in urban areas. Section VI presents a number of sensitivity analyses, and Section VII concludes.